Hedging Pressure Effects in Futures Markets - De Roon, Frans A.; Nijman, Theo E.; Veld, Chris (Journal of Finance, 2000)
We present a simple model implying that futures risk premia depend on both own‐market and cross‐market hedging pressures. Empirical evidence from 20 futures markets, divided into four groups (financial, agricultural, mineral, and currency) indicates that, after controlling for systematic risk, both the futures own hedging pressure and cross‐hedging pressures from within the group significantly affect futures returns. These effects remain significant after controlling for a measure of price pressure. Finally, we show that hedging pressure also contains explanatory power for returns on the underlying asset, as predicted by the model.